Cover Image, Volume 22, Issue 3. Issue 3 (18th February 2020) - Matza, Louis S.; Boye, Kristina S.; Stewart, Katie D.; Coyne, Karin S.; Wullenweber, Paula K.; Cutts, Katelyn N.; Jordan, Jessica B.; Wang, Qianqian; Yu, Maria; Currie, Brooke M.; Malley, Karen G.; Ishak, K. Jack; et al.
Abstract : The outside back cover image is based on the Original Article Crossover Clinical Trial Assessing Patient PREFERence between the Dulaglutide Pen and the Semaglutide Pen (PREFER) by Louis S. Matza, Katie Stewart, KARIN S. COYNE et al., https://doi.org/10.1111/dom.13902 . Abstract : The outside back cover image is based on the Original Article Crossover Clinical Trial Assessing Patient PREFERence between the Dulaglutide Pen and the Semaglutide Pen (PREFER) by Louis S. Matza, Katie Stewart, KARIN S. COYNE et al., https://doi.org/10.1111/dom.13902 .